Genetic association analysis of ATG16L1 rs2241880, rs6758317 and ATG16L2 rs11235604 polymorphisms with rheumatoid arthritis in a Chinese population - Mo, Ji-Jun; Zhang, Wei; Wen, Qin-Wen; Wang, Ting-Hui; Qin, Wen; Zhang, Zhen; Huang, Hua; Cen, Han; Wu, Xiu-Di (International immunopharmacology, 2021)
•The ATG16L1 rs2241880 was associated with RA, CCP-positive RA and RF-positive RA.•Interaction between rs2241880 and rs11235604 was associated with RA.•Interaction between rs6758317 and rs11235604 was associated with RA, CCP-positive RA and RF-positive RA. This study was performed to test whether ATG16L1 rs2241880, rs6758317 and ATG16L2 rs11235604 polymorphisms were associated with RA and further examine the genetic interaction between ATG16L1 and ATG16L2 in RA among a Chinese population. A total of 594 RA patients and 604 healthy controls were included, and the genetic polymorphisms were genotyped based on HI-SNP technology. Significant associations of ATG16L1 rs2241880 polymorphism with RA (T/T versus C/T + C/C, OR = 1.32, 95% CI 1.04–1.67, P = 0.02), cyclic citrullinated peptide (CCP)-positive RA (genotype comparison, P = 5.38 × 10−3; T/T versus C/T + C/C, OR = 1.45, 95% CI 1.12–1.87, P = 4.86 × 10−3) and rheumatoid factor (RF)-positive RA (genotype comparison, P = 0.03; T versus C, OR = 1.23, 95% CI 1.01–1.49, P = 0.04; T/T versus C/T + C/C, OR = 1.44, 95% CI 1.10–1.88, P = 7.62 × 10−3) were found. Significant genetic interaction between ATG16L1 rs2241880 and ATG16L2 rs11235604 was associated RA (P = 0.03), and significant genetic interaction between ATG16L1 rs6758317 and ATG16L2 rs11235604 was associated with RA (P = 7.57 × 10−3), CCP-positive RA (P = 0.01) and RF-positive RA (P = 0.01). Consistently, stratification analysis found that significant associations of RA with ATG16L1 rs2241880, rs6758317 polymorphisms were only detected among individuals carrying C/T genotype of the ATG16L2 rs11235604 polymorphism. Our results indicated that ATG16L1 rs2241880 polymorphism was associated with RA in Chinese population, and provided evidence for genetic interaction between ATG16L1 and ATG16L2 in determing the development of RA, highlighting the involvement of autophagy in the pathogenesis of RA.